2014
DOI: 10.3852/13-045
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and phylogenetic position of Fomitiporia torreyae, a causal agent of trunk rot on Sanbu-sugi, a cultivar of Japanese cedar (Cryptomeria japonica) in Japan

Abstract: Trunk rot poses a substantial threat to Sanbu-sugi, one of the most economically important cultivars of Japanese cedar (Cryptomeria japonica). The etiology of this disease, including its main agents, is incompletely known. This trunk rot was attributed to Fomitiporia (Phellinus) hartigii or F. (Phellinus) punctata. Here we phylogenetically analyzed DNA sequences of four markers from a set of strains isolated from trunk-rot symptoms and recovered a single, monophyletic clade, indicating that a single taxon is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Fungal DNA was extracted from mycelia as described in Ota et al (2014) [ 35 ]. Cultures were grown in 10 mL MYG medium (2% malt extract, 0.2% yeast extract, and 2% glucose) at 25°C in the dark and were harvested 7 days after inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…Fungal DNA was extracted from mycelia as described in Ota et al (2014) [ 35 ]. Cultures were grown in 10 mL MYG medium (2% malt extract, 0.2% yeast extract, and 2% glucose) at 25°C in the dark and were harvested 7 days after inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…The researches on Fomitiporia have receieved great attention because of their curative properties these years. It reported that the fungus is particularly rich in pregnenolone type triterpenes and exhibited positive effects on treating cancer (Ota et al, 2014;Chepkirui et al, 2018). In this way, the three fungi would be good candidates as materials for developing food or medicines.…”
Section: Introductionmentioning
confidence: 99%
“…F. torreyae was also reisolated from all infected plants. The fungus has been previously reported to cause trunk rot of Japanese cedar in Japan (Ota et al 2014(Ota et al , 2016, but this is the first report of F. torreyae causing trunk rot of Chinese torreya in Anhui Province of China.…”
mentioning
confidence: 84%